Trends among quantity surveying's graduates in pursuing postgraduate studies - Wong, Ming Yien, 1986-, author; Razali Abdul Hamid, supervisor; Fakulti Alam Bina (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2010)
Project Paper (Sarjana Muda Ukur Bahan) - Universiti Teknologi Malaysia, 2010